Obstacles to inclusion- perceptions of teachers from Bosnia and Herzegovina - Biscevic, Inga; Zecic, Sadeta; Mujkanovic, Elvira; Mujkanovic, Edin; Memisevic, Haris (Special Education, 2017)
Inclusive education is increasingly becoming a dominating paradigm of the educational system in Bosnia and Herzegovina. However, although supported by positive legislature, there are still numerous obstacles to inclusion. The goal of the present study was to examine the attitudes of regular education teachers towards inclusive education, more specifically towards obstacles to successful inclusion. The sample consisted of 200 elementary school teachers from two cantons in Bosnia and Herzegovina. The greatest obstacle for inclusion as perceived by the teachers was the lack of professionals trained to work with children with special educational needs in regular schools. It is of utmost importance to support regular education teachers in their efforts to support all students in their classes. This calls for a more meaningful and thorough reformation of regular schools.
Keywords: inclusive education; obstacles to inclusion; teachers; Bosnia and Herzegovina